Representasi Green Economy Dalam Iklan Digital: Studi Semiotika Kampanye Produk Ramah Lingkungan - Maulana Syawaldi (Global Journal of Management, Accounting, and Financial Studies, e-ISSN: 3109-1539, 2025)
This study aims to analyze the representation of the green economy in digital advertising through a semiotic approach. Amid growing public awareness of environmental issues, many companies are utilizing digital media to promote environmentally friendly products. However, there has been little research specifically examining how symbols and sustainability messages are constructed in digital advertisements. Using a qualitative approach with semiotic analysis, this research examines the visual elements, symbols, texts, and imagery used in digital advertisements for eco-friendly products. Advertisement samples were obtained from various digital platforms such as social media and websites featuring sustainability campaigns. The results show that green and blue colors dominate the visual elements of advertisements to create associations with nature, freshness, and cleanliness. Symbols such as trees, leaves, and water are consistently used to represent sustainability values. The texts in the advertisements include phrases like “eco-friendly,” “organic,” and “sustainable,” aiming to instill a positive perception of the products. Imagery portraying green activities such as cycling or recycling functions to build a narrative that consuming such products is an ethical and responsible act. The analysis also finds that the symbols and narratives in advertisements shape consumer perceptions that choosing eco-friendly products is part of a modern and environmentally conscious lifestyle. These findings affirm that digital advertising serves not only as a marketing tool but also as an educational medium in shaping consumer attitudes toward environmental issues. This study makes an important contribution to the field of advertising semiotics and expands the understanding of the role of visual communication in supporting the green economy agenda